2016
DOI: 10.1007/s00213-016-4417-4
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-receptor antagonism increases pain and decreases pleasure in obese and non-obese individuals

Abstract: Despite having higher levels of baseline beta-endorphin and altered beta-endorphin-reactivity to naltrexone, obese individuals reported a similar increase in pain and decrease in pleasantness following naltrexone compared to non-obese individuals. Beta-endorphin levels did not correlate with pain or pleasantness in either group, but naltrexone-induced changes in pain and pleasantness were mildly correlated. Moreover, naltrexone-induced changes in pain were related to depression scores, while naltrexone-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The μ-opioid system modulates both reward and pain across species. For instance, stimulating μ-opioid receptor (MOR) with non-sedative doses of opioid drugs leads to an increased preference for sweet and fatty foods in both rats and humans, while opioid antagonists blunt the effect of these foods as positive reinforcers (Fantino et al, 1986; Yeomans and Gray, 1996, 1997; Ziauddeen et al, 2012; Eikemo et al, 2016; Price et al, 2016). The same pattern of MOR effects have been observed in healthy humans in response to monetary (Weber et al, 2016; Eikemo et al, 2017) and social rewards (Chelnokova et al, 2014; Chelnokova et al, 2016; Buchel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The μ-opioid system modulates both reward and pain across species. For instance, stimulating μ-opioid receptor (MOR) with non-sedative doses of opioid drugs leads to an increased preference for sweet and fatty foods in both rats and humans, while opioid antagonists blunt the effect of these foods as positive reinforcers (Fantino et al, 1986; Yeomans and Gray, 1996, 1997; Ziauddeen et al, 2012; Eikemo et al, 2016; Price et al, 2016). The same pattern of MOR effects have been observed in healthy humans in response to monetary (Weber et al, 2016; Eikemo et al, 2017) and social rewards (Chelnokova et al, 2014; Chelnokova et al, 2016; Buchel et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, initial evidence of opioid modulation of pleasantness and fMRI responses to rewarded decisions in humans is modest but consistent with the evidence that opioids promote the pleasantness of rewards received outside of a decision context (Chelnokova et al, 2014, 2016; Drewnowski et al, 1992; Eikemo et al, 2016; Murray et al, 2014; Price et al, 2016; Yeomans, 1995; Yeomans & Gray, 2002). Whether opioid agonist drugs increase the liking of choice outcomes in humans remains to be seen.…”
Section: Review Of Studies On Decision-makingmentioning
confidence: 57%
“…A recent review of positron emission tomography (PET) studies with opioid receptor-specific tracers posit a central role of the opioid system for positive affective states (Nummenmaa & Tuominen, 2017). Drug studies in both human and nonhuman animals show that blocking opioids reduces food pleasantness and consumption, especially for high-calorie foods (Drewnowski, Krahn, Demitrack, Nairn, & Gosnell, 1992; Eikemo et al, 2016; Price, Christou, Backman, Stone, & Schweinhardt, 2016; Yeomans, 1995; Yeomans & Gray, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, another author demonstrated that naltrexone as an opioid-receptor antagonist influences pain tolerance. Also, he showed that naltrexone-induced changes in pain were correlated with depression scores [39].…”
Section: Discussionmentioning
confidence: 99%